Ku teoretycznej wielości (w sprawie teorii słabych) - Januszkiewicz, Michał (Przestrzenie Teorii, 2007)
This article refers to the problems of disputes over the concept of a literary character and theory (in humanities). The reference to the historical perspective becomes an occasion for the presentation of an attitude which stems from post-modern reflection: the metaphysical (essential) claims are put forward both to the subject and to the manner of studies, they are lifted for the sake of pragmatic and hermeneutic interpretations within this which the author calls weak theories (and the conception of weakness is here in a distinct relationship with philosophical proposals formulated by Gianni Vattura).